Nanostructured protective coating systems, fireproof and environmentally friendly, suitable for the protection of metallic substrates - Pereyra, Andrea Marisa (2010)
The aim of this study was to formulate, develop, and determine the behavior of nanostructured protective coating systems, fireproof and environmentally friendly, suitable for the protection of metallic substrates. The results allowed concluding that the di- and tripigmented formulations based on laminar zinc, either alone or mixed with nanozinc, showed an excellent corrosion resistance when a nanostructured self-cured inorganic silicate (high silica/alkali ratio) was selected as the film forming material. Coating systems included a sealer of low permeability, which was based on the same film forming material that primers and on laminar pigments. Intumescent coatings were manufactured and then applied on the sealer; in this study, two types of products in an aqueous single package were formulated. The anticorrosive capacity was evaluated in a salt spraying (fog) chamber and in a 100% relative humidity cabinet while the performance against the fire action was determined by estimating the limiting oxygen index in the LOI cabinet, the flame advance in an inclined tunnel, and, finally, the thermal conductivity in a UL 94 flame chamber; in the last test, the degree of intumescence was also assessed. The results showed an excellent ability for corrosion controlling and, in addition, a good performance against the fire action of some of the no pollutant coating systems designed.